Safety of íntravitreal panitumumab combined with intravitreal ranibizumab in rabbits - Bikbov, Mukharram; Kazakbaeva, Gyulli M.; Valishin, Iskander D.; Ishbulatova, Aigul M.; Panda-Jonas, Songhomitra; Mustafina, Gulshat R.; Jonas, Jost B. (PLOS ONE, 2025)
Purpose: To examine the safety of intravitreally applied epidermal growth factor (EGF) receptor antibody panitumumab combined with intravitreally injected vascular endothelial growth factor (VEGF) antibody ranibizumab in rabbits. Methods: The experimental study included 8 male rabbits (age: 2−3 months; weight: 2.5-2.6 kg). The right eyes received three intravitreal injections of panitumumab (1 mg in 0.10 mL) combined with intravitreal injections of ranibizumab (0.5 mg in 0.05 mL) in intervals of 4 weeks, while the left eyes received three double intravitreal injections of Ringer´s solution (0.10 mL and 0.05mL). At baseline, at the time points of the re-injections, and at 2 weeks and at 6 weeks after the last injection, the animals were examined by fundus photography and optical coherence tomography (OCT). At study end at 2 weeks after the last injection for 4 animals (total study duration: 10 weeks) or at 6 weeks after the last injection for the remaining 4 rabbits (total study duration: 14 weeks), the animals were sacrificed and the eyes were histomorphometrically examined. Results: The right eyes (study eyes) and left eyes (control eyes) did not differ significantly in cell count of the retinal ganglion cell layer (8.5 ± 8.3 cells per 150µm versus 4.5 ± 3.3 cells;P = 0.04), inner nuclear layer (33.1 ± 14.0 cells versus 49.0 ± 22.3 cells;P = 0.04) and outer nuclear layer (133.7 ± 50.0 cells versus 171.3 ± 75.3 cells;P = 0.07) nor in mean thickness of the ganglion cell layer (31.8 ± 34.4µm versus 24.3 ± 15.2µm;P = 0.15), inner plexiform layer (32.4 ± 48.2µm versus 25.6 ± 11.2µm;P = 0.22), inner nuclear layer (26.6 ± 14.0µm versus 26.7 ± 10.2µm;P = 0.43), outer plexiform layer (6.6 ± 3.7µm versus 6.8 ± 2.0µm;P = 0.07), outer nuclear layer (32.6 ± 16.1µm versus 30.6 ± 11.8 µm;P = 0.82) and of total retina (157.7 ± 99.4µm versus 152.0 ± 60.7µm;P = 0.34). Apoptotic cells were not detected in either group. Mean IOP did not differ significantly between the right eyes (study eyes) and the left eyes (control eyes). Intravital signs of intraocular toxicity were not detected. Conclusions: Repeatedly intraocularly applied panitumumab combined with ranibizumab was intraocularly well tolerated and did not differ in the ocular reaction from intravitreal injections of Ringer´s solution.
Veröffentlicht: 16. Dezember 2025
Gesehen am 19.02.2026